Conversion of T Effector Cells Into T Regulatory Cells in Type 1 Diabetes/Latent Autoimmune Diabetes of Adults by Inhibiting eIF5A and Notch Pathways - Rafiqi SI; Aldasouqi A; Paparodis RD; Dewan S; Farooqi A; Faisal S; Nemat Y; Salim N; Qureshi S; Mahmood A; Tovar Y; Jun JY; et al. (ImmunoTargets and Therapy)
Shafiya Imtiaz Rafiqi,1,2 Ahmad Aldasouqi,1– 3 Rodis D Paparodis,4,5 Sandesh Dewan,1,2 Aneeba Farooqi,1,2 Sarah Faisal,1,6 Yousuf Nemat,1,7 Nancy Salim,1,2 Salauddin Qureshi,1,8 Asif Mahmood,9 Yara Tovar,1,2 John Y Jun,1,2 Andrea L Kalinoski,10 Raghavendra G Mirmira,11 Juan Carlos Jaume,5 Shahnawaz Imam1,2 1Division of Endocrinology, Diabetes and Metabolism, Department of Medicine, College of Medicine and Life Sciences, University of Toledo, Toledo, OH, USA; 2Center for Diabetes and Endocrine Research (CeDER), College of Medicine and Life Sciences, University of Toledo, Toledo, OH, USA; 3College of Natural Sciences and Mathematics, University of Toledo, Toledo, OH, USA; 4Hellenic Endocrine Network, Athens, Greece, Endocrinology, Diabetes and Metabolism Clinics, Private Practice, Patras, Greece; 5Stritch School of Medicine/Edward Hines, Jr. VA Hospital, Loyola University Chicago, Hines, IL, USA; 6College of Art and Science, Case Western Reserve University, Cleveland, OH, USA; 7Florida Atlantic University, Boca Raton, FL, USA; 8Division of Biological Standardization, ICAR-Indian Veterinary Research Institute, Izatnagar, Bareilly, India; 9University of Toledo Medical Centre, Hospital Medicine, University of Toledo, Toledo, OH, USA; 10Department of Surgery, Integrated Core Facilities, University of Toledo, Toledo, OH, USA; 11Division of the Biological Sciences, the University of Chicago, Chicago, IL, USACorrespondence: Shahnawaz Imam, Center for Diabetes and Endocrine Research (CeDER), College of Medicine and Life Sciences, BHS386, Mail Stop 3000 Arlington Ave. University of Toledo, Toledo, OH, 43614-2598, USA, Tel +1 419-383-3786, Email shahnawaz.imam@utoledo.eduBackground: The generation of functionally active, stable T regulatory cells (Tregs) is a crucial target of type 1 diabetes (T1D) immunotherapy. This study investigated therapeutic intervention for T1D/Latent autoimmune diabetes in adults (LADA), wherein the diabetogenic proinflammatory Treg (intermediate) cell subset was characterized and driven to a Treg phenotype (CD4+CD25+FOXP3+). This involved simultaneous inhibition of the eukaryotic initiation factor 5a (eIF5a) and Notch pathways using GC7 (N1-Guanyl-1,7-diaminoheptane) and Anti-DLL4 (Delta-like-ligand-4).Methods: Peripheral blood from patients with T1D/LADA and healthy adults (n=7 each) was used to isolate the CD4+CD25− T cell population and CD4 deficient peripheral blood mononuclear cells (PBMCs). Cells were subjected to GAD65+GC7+anti-DLL4 treatment for seven days and compared with conventional anti-CD3/CD28/CD137 stimulation for conversion into the Tregs. Newly plasticized Tregs were assessed for their suppressive potential against freshly isolated autologous T responder cells. In addition, live, dead, and apoptotic cell counts were performed to evaluate the adverse effects of immunomodulatory treatment on immune cells. The data was analyzed with GraphPad Prism using 1- or 2-way ANOVA and a Student’s t-test.Results: A unique population of proinflammatory cytokines expressing intermediate Tregs (CD4+CD25−IFNg+IL17+FOXP3+) was characterized in T1D/LADA patients and found significantly increased compared to age-matched healthy adults. Simultaneous inhibition of eIF5a and Notch pathways could induce Treg phenotype in Treg-deficient CD4+ T cells and CD4 deficient PBMCs from T1D/LADA patients. GAD65+GC7+anti-DLL4 treatment plasticized Tregs withstanding a proinflammatory milieu mimicking T1D/LADA, and the plasticized Tregs exhibited a stable and suppressive functional phenotype. Furthermore, GAD65+GC7+anti-DLL4 treatment had no adverse effects on immune cells.The present approach is a multipronged approach involving the inhibition of eIF5a and Notch pathways that addresses the upregulation of immune tolerance, differentiation, and proliferation of cytotoxic T cells and alleviates β-cell dysfunction. Additionally, this treatment strategy could also be leveraged to boost Treg generation following islet transplantation or as a combinational therapy along with adoptive cell transfer.Keywords: autoimmune disorders, eIF5a, immunomodulation, immune cell plasticity, latent autoimmune diabetes in adults, notch, transdifferentiation, type 1 diabetes, unfit tregs